2010
DOI: 10.1037/a0020790
|View full text |Cite
|
Sign up to set email alerts
|

Minority stress, perceived bicultural competence, and depressive symptoms among ethnic minority college students.

Abstract: Based on biculturalism theory (LaFromboise, Coleman, & Gerton, 1993), the present study examined the direct effect of perceived bicultural competence (PBC) on depressive symptoms, and PBC as a potential coping resource to moderate the association between minority stress and depressive symptoms. Participants were 167 Asian American, African American, and Latino/a American students at a predominantly White Midwest university. Results from a hierarchical regression analysis suggested that (a) minority stress was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 40 publications
(96 reference statements)
9
129
1
2
Order By: Relevance
“…Instead, when both stress variables were considered simultaneously in the regression analyses, only college stress contributed unique variance to students' persistence intentions. These findings are not consistent with previous studies that have shown that among ethnic minority students, including Hispanics, minority status stress contributed unique variance to lack of psychological well-being when controlling for general college stress (Arbona & Jimenez, 2014;Rodriguez et al, 2000;Smedley, 1993;Wei et al, 2010). Taken together, these findings suggest that college stressors may have a greater bearing on students' college persistence decisions than minority status stressors, which appear to have a stronger relation to feelings of wellbeing even after college stress has been taken into account.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Instead, when both stress variables were considered simultaneously in the regression analyses, only college stress contributed unique variance to students' persistence intentions. These findings are not consistent with previous studies that have shown that among ethnic minority students, including Hispanics, minority status stress contributed unique variance to lack of psychological well-being when controlling for general college stress (Arbona & Jimenez, 2014;Rodriguez et al, 2000;Smedley, 1993;Wei et al, 2010). Taken together, these findings suggest that college stressors may have a greater bearing on students' college persistence decisions than minority status stressors, which appear to have a stronger relation to feelings of wellbeing even after college stress has been taken into account.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have shown that minority status stress is positively associated to psychological distress when controlling for general college stress. These studies have included exclusively Hispanic college samples (Arbona & Jimenez, 2014;Rodriguez et al, 2000;Saldaña, 1994) and heterogeneous groups of African American, Asian and Hispanic students (Smedley et al, 1993;Wei et al, 2010). While there is evidence that the experience of psychological distress is negatively related to college students' grade point average and degree completion (Eisenberg, Golberstein, & Hunt, 2009), only one study was located that examined the relation of ethnic minority status stress to college persistence.…”
Section: Consuelo Arbona 13mentioning
confidence: 99%
See 1 more Smart Citation
“…While this may be a good sign for the United States, unfortunately, students of color are met with additional challenges such as their minority status (Morrison, 2010;Prillerman, Myers, & Smedley, 1989;Smedley et al, 1993;Wei et al, 2010) along with other problems (e.g. socioeconomic and first-generation statuses) they bring to college (Means et al, 2016;Aud, Fox & KewalRamani, 2010;Engle & Tinto, 2008).…”
Section: Cultural Background In Higher Educationmentioning
confidence: 99%
“…socioeconomic and first-generation statuses) they bring to college (Means et al, 2016;Aud, Fox & KewalRamani, 2010;Engle & Tinto, 2008). In addition, often times, students of color are making transitions from racially segregated neighborhoods and high schools to predominantly white institutions (Keels, 2013;Wei et al, 2010). Therefore, the following information below will focus on the additional challenges students of color have encountered in predominantly white institutions and how these challenges make it difficult for them to take advantage of the college's resources for their learning and personal development in college.…”
Section: Cultural Background In Higher Educationmentioning
confidence: 99%